2018
DOI: 10.1186/s12883-018-1027-2
|View full text |Cite
|
Sign up to set email alerts
|

A digital assessment system for evaluating kinetic tremor in essential tremor and Parkinson’s disease

Abstract: BackgroundSpiral drawing on papers is a common tremor evaluation tool for diagnosing patients with essential tremor (ET) or Parkinson’s disease (PD). No standard drawing methods and parameters that use graphic tablets are yet available for objective evaluation.MethodsThis study established a tremor assessment system for tremor severity by using graphic tablets. Twelve patients with ET and twelve patients with PD were tested to establish system algorithms, and six additional patients were tested with the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…We refer to two studies, the first being the work by Lin et al [12], where the authors reported Pearson's correlations between the VRS and the investigated signal-derived parameters to be as high as 0.973. The models of VRS were trained and validated with digitized spiral drawings from ET and PD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We refer to two studies, the first being the work by Lin et al [12], where the authors reported Pearson's correlations between the VRS and the investigated signal-derived parameters to be as high as 0.973. The models of VRS were trained and validated with digitized spiral drawings from ET and PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…We recognize this generalizability issue as very important in the context of targeting the kinetic tremor, as this symptom is widespread in ET. Combining data from PD and ET patients would allow for better comparison with, e.g., work by Lin et al [12]. However, one should be aware that, during the model fitting, such a combination may result in discarding parameters that are specific for only one of the diseases, yielding models that are more general, albeit with inferior prediction quality when tested solely in PD or ET populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While not making direct measurements, dexterity can be judged by the quality of the line left on the screen. The speed, acceleration and execution time of the drawings / tasks can also be related to the degree of loss of functionality of the hands [16].…”
Section: Reviewmentioning
confidence: 99%